Analysis of Juvenile Laws and their Protection of Juvenile Offenders in Pakistan (Journal of Social Sciences Review, 2023)
This research article aims to analyze the current laws and regulations in Pakistan that pertain to juvenile offenders and their protection. The article will examine international legislation on the rights of children, including the Convention on the Rights of the Child 1989, Minimum Guidelines for Youthful Justice 1980, Article 77 of Additional Protocol-II 1977, and the Child Rights Declaration 1924. The article will also examine the national legislation in Pakistan, including the Penal Code of 1860, the Reformatory Schools Act of 1897, the Smoking Ordinance, the Probation Ordinance of 1960, and the Child Marriage Restraint Act of 1929. The article will further explore the scope of the Probation Ordinance 1960 and the constitutional provisions relating to children. The research will provide an in-depth analysis of the current laws and regulations in Pakistan that protect the rights of juvenile offenders and assess the extent to which these laws are being implemented effectively.
Keywords: Juvenile Laws; Juvenile Offenders; Protection; Pakistan; International Legislation; Convention on the Rights of the Child; Youthful Justice; Constitutional Provisions